Measurement and prediction of drilling force in fresh human cadaver mandibles: A pilot study. (3rd December 2019) - Yu, Dedong; Liu, Chang; Wu, Yiqun; An, Qinglong
Abstract: Background: Bone drilling is a vital procedure in implant surgery and dental implant training systems based on virtual reality technology. Purpose: Predict and update drilling force in real time based on a virtual dental implant training system and lay the foundation for realizing force feedback in dental implant training instruments. Materials and Methods: An experimental platform was established to measure the drilling force for human mandibles from donors of different ages. Response surface methodology was applied to analyze the drilling force. Results: Force regression equations for different age groups were acquired. The order of the effects (from greatest to least) of the drilling parameters on the drilling force was the drill bit diameter, feed rate, and rotational speed. To obtain the minimum force, higher rotational speeds, lower feed rates, and smaller diameters were preferred within the range of commonly used medical reference parameters of bone drilling. Conclusion: The experimental data were confirmed to be scientific for the predicted models of drilling force.